2010
DOI: 10.1111/j.1530-0277.2009.01140.x
|View full text |Cite
|
Sign up to set email alerts
|

NeoHepatocytes From Alcoholics and Controls Express Hepatocyte Markers and Display Reduced Fibrogenic TGF‐β/Smad3 Signaling: Advantage for Cell Transplantation?

Abstract: Generation of NeoHepatocytes from alcoholics, displaying several features of human hepatocytes, offers new perspectives for cell therapeutic approaches, as cells can be obtained repeatedly in a noninvasive manner. Furthermore, the autologous setting reduces the need for immunosuppressants, which may support recovery of patients which are declined for liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Furthermore, we have shown that myostatin induces the expression of selected lipogenic genes and increases lipid accumulation in the cultured liver cells. This finding is congruent with the reports that TGFβ1, which shares the type I receptor with myostatin, induces lipogenic gene expression and increases lipid accumulation in liver cells [42], [43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we have shown that myostatin induces the expression of selected lipogenic genes and increases lipid accumulation in the cultured liver cells. This finding is congruent with the reports that TGFβ1, which shares the type I receptor with myostatin, induces lipogenic gene expression and increases lipid accumulation in liver cells [42], [43].…”
Section: Discussionsupporting
confidence: 92%
“…There was no effect of myostatin on fatty acid oxidation measured in parallel (data not shown). To our knowledge, this is the first report of direct pro-lipogenic effect of myostatin on liver cells, although others have shown that TGFβ1, which shares similar post-receptor signaling pathways with myostatin, increases SCD-1 expression and increases lipid storage in cultured liver cells [42], [43].…”
Section: Resultsmentioning
confidence: 75%
“…Previous data from our group have shown that during conversion to PCMO the monocytes’ response towards exogenous TGF-β1 is changing with respect to Smad2 and Smad3 activation in such a way that they become sensitive to Smad2C and insensitive to Smad3C phosphorylation [ 32 ]. Given the presence of activin A and TGF-β1 in the culture supernatants and thus the existence of a self-stimulatory/autocrine signaling loop in these cells, we hypothesised that the sensitivity of PCMO to endogenous Smad-activating agents is altered in a similar way.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, transplantation of neohepatocytes with excellent quality might help patients suffering from acute or acute-on-chronic liver disease, bridging the time for whole-organ transplantation or support the regeneration of the liver. Recently, we could show that neohepatocytes might have a survival or proliferation advantage compared to primary human hepatocytes due to reduced Smad1 and Smad3 expression (13).…”
Section: Discussionmentioning
confidence: 99%